EPISTEMOLOGI HALAL DAN APLIKASINYA - Syamsuddin Arif (DIRASAT: Jurnal Studi Islam dan Peradaban, 2019)
This paper investigates the Islamic legal concept of ḥalāl (‘allowed’) and closely related notions, ṭayyib (‘good’) and ṭāhir (‘clean, pure’), as well as the opposite concepts including ḥarām (‘forbidden’), najis (‘filthy’), shubhat (‘vague’), and ḍarūrat (‘forced’) as they are outlined in the Qur’an and Hadith from epistemological and philosophical perspectives. Moreover, it will deal with the Islamic ruling on consumer products that are derived from forbidden materials and have undergone natural or chemical transformation (istiḥālah). By so doing, the paper is not only highlighting the flexible nature of Islamic law but also exploring the relationship between religion, law and science.